Natural Gas Migration Pathways and Their Influence on Gas Hydrate Enrichment in the Qiongdongnan Basin, South China Sea - Tingna Zuo; Ren Wang; Yulin He; Wanzhong Shi; Jinqiang Liang; Litao Xu; Hao Du; Yan Deng; Xiaofeng Xu (Geofluids)
2D and 3D seismic data and basin simulation were used to investigate the gas hydrate distribution and natural gas migration pathways in the Qiongdongnan Basin (QDNB). Hydrate-related amplitude anomalies and extensive bottom simulating reflectors (BSRs) were mapped within the uppermost part. Based on their seismic reflection characteristics, the three main types of natural gas migration pathways and their distributions in the QDNB were identified through high-resolution seismic data. Basin modeling was carried out to document the migration efficiency of different migration pathways and their effects on hydrate enrichment. The basin modeling results show the following: (1) Diapirs, fault structures, and fractures constitute the three main types of natural gas migration pathways that transport the thermogenic gas from the deep to shallow layers in the QDNB. (2) The three migration pathways impact hydrate enrichment in different ways. Diapirs and faults contribute significantly to hydrate enrichment due to their higher migration efficiency. In comparison, the migration efficiency of the fracture systems is lower, with minimal benefit to hydrate enrichment. (3) The natural gas hydrate in the QDNB is mainly distributed along the diapirs and deep faults and generally scattered around the fracture system. These conclusions indicate that the migration pathways in the QDNB are regionally distributed and are closely related to hydrate accumulation.